Screening of volatile organic compounds emitted from different packaging materials: case study on fresh-cut artichokes - Ashraf, Jahan Zaib; Pati, Sandra; Fatchurrahman, Danial; Amodio, Maria Luisa; Colelli, Giancarlo (Frontiers in Sustainable Food Systems, 2023)
In the present work, the emission of volatile organic compounds (VOCs) from plastic packaging materials and their migration to the packaged product was investigated. Fresh-cut artichokes were chosen as a case study owing to their nutritional profile, including phenolic compounds, antioxidants, inulin and fiber, and the high market demand. Artichokes were cut into quarters, packaged in active modified atmosphere (5% O2 and 10% CO2) in three different micro-perforated (MP) packages (polypropylene (PP), polypropylene/polyamide (PP/PA) and polylactic acid (PLA)) and stored for 10 days at 5° C. For the detection of VOCs on the packaging materials and in the packaged product, three approaches were considered. First, VOCs emitted from a piece of package were extracted by solid phase micro extraction (SPME), at 30°C, and analyzed by gas-chromatography coupled to mass spectrometry (GC–MS). Second, VOCs from the headspace of the empty closed bag were extracted by SPME, at 5°C, to understand if any packaging volatile compound was transferred into the package atmosphere in this temperature condition. Finally, packaged artichokes were also analyzed by SPME/GC–MS to detect any presence of packaging volatiles compared to the fresh product. Emitted VOCs were different according to the material; in particular PP/PA emitted the greatest number of VOCs, most of them belonging to the class of branched alkanes and alkenes, such as 4-methyl-heptane, 2,4-dimethyl-heptane, 4-methyl-octane and 2,4 dimethyl heptene; PP emitted octane, aldehydes, and 1-metoxy-2-propanol; PLA emitted aldehydes and propanoic acid. Some VOCs were found into the atmosphere of the empty bags as well as on packaged artichokes, while they were not found in the fresh samples before packaging, suggesting that a study on the emission of VOCs from different plastic materials in contact with food and on the effect of different storage conditions is very critical for a better understanding of this issue.